Соціонічний аналіз як інструмент оптимізації якісного складу малих груп - Морушко, Олександр; Андрейчук, Станіслав Казимирович (Видавництво Львівської політехніки, 2018)
Talent management has become increasingly importance as a factor in increasing the competitiveness of enterprises, success in achievement its development strategy. In this context, attach great rational importance to the use of human resource, in order to realize its potential, according to natural abilities. This should contribute to be a relatively socionic analysis method. The vitality of a small social group largely depends on the psychological compatibility of the participants in this group. In addition to the formally established among members of the organization of job subordination, there is a complex system of informal ties, which can be optimized through socionic analysis.
Keywords: малі групи; соціонічний аналіз; управління персоналом; психологічна дистанція